(3GdedMeI GdadSWjfjIs (3ebGdGJ ddaja ef GdcJGH hGdeacQjf GdYQHs - (3GdMGL, CMeOs; (3EHQGgje, CejQIs; (3GdCUhQ, NGdOs; (3GdLfGHj, CMeO cSGQs; (3GdMSf, eMehOs; (3GdMeGej, gTGes; (3GdOTfGhj, eHGQcs; (3GdQejS, fgis; (3GdTQja, CMeOs; (3GdUQGa, hdjOs; (3GdUYjH, EVMhjs; (3GdYJhe, Cjefs; et al. ((3GdbGgQIs (3GdafGQs, 2023)
(3eG TgOJg hJTgOg ZRI GdadSWjfjI MGdI fGOQI de jcO GdJGQjN GdHTQj jTgO dgG eKjkdG ef bHd (B.. (3EfgG HMb (B- (3edMeI GdJGQjN cdg aajeG hQGA GdOjchQGJ GdeUWfYI ddbjGOI GdESQGFjdjI (B. . (3hajeG hQGA GfaYGdGJ fJjGgh GdJj JYcS HhVhM MjQI hbdbG (B.. (3hceG JhbYfG cGf MLe GdGSJLGHI ef GdcJGH Ydi GeJOGO GdhWf GdYQHj dGakJG ddfXQ, EP TeQ fMh CQHYjf efge Yf SGYO GdacQ, hLGHhG HCbdGege eMGhQ GdbVjIJ ef HJOGgG Edi efJgGgG hSGbhG CLhHI TGajI dCSFdI eYbOI cd MSH QDjJg hefXhQgs
Keywords: (3GdGfJaGVI GdadSWjfjIs; (3GdfRGY GdYQHj GdESQGFjdjs; (3GdfRGY GdYQHj GdESQGFjdjs